Mechanisms of Chinese Hickory Resistance to Dry Rot Disease by Botryosphaeria dothidea: A Comprehensive Analysis from Gene Expression to Non-Coding RNAs - Yingshan Chen; Yuke Zhou; Jiahui Chen; Haoming Cai; Ruifeng Yang; Da Zhang; Youjun Huang (Plants)
Chinese hickory (Carya cathayensis) is an important tree species for agriculture, but dry rot disease, caused by Botryosphaeria dothidea, threatens its viability. To study the interactions between the tree and the pathogen, transcriptomic sequencing was conducted on infected and healthy tissues from field-grown hickory. Differential gene expression analysis identified key defense pathways and genes activated during infection. The study also explored the roles of non-coding RNAs, such as lncRNAs and circRNAs, in the tree’s defense. The results showed that during the early and mid stages of infection, the tree defends itself through mechanisms like enhanced lignin synthesis and increased peroxidase activity. Non-coding RNAs contribute to disease resistance by reinforcing the cell wall, increasing oxidase activity, and promoting the synthesis of antibiotic-related secondary metabolites. Additionally, gene expression patterns at these stages differ significantly from those at the late stage of infection, when most disease resistance pathways are suppressed, and genes like PR1 and WRKY2 show a decline. These findings offer valuable insights into the pathogenesis of Chinese hickory dry rot disease and potential strategies for improving resistance.